Strategy Of Using Video And Audio Narration In Online Media To Increase Audience Engagement - zakia Askanabila; Martha Heriniazwi Dianthi; Yanto Yanto (Journal of Multidisciplinary Research, 2026)
This study aims to analyze the strategy of Bengkuluekspress.com in utilizing news videos and audio narration to increase audience engagement on digital platforms. This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The research informants consisted of five individuals directly involved in the multimedia content production process, including the General Manager, Editor-in-Chief, Content Manager, Video Editor, and Voice Over. Data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. This study applies the Uses and Gratifications Theory (UGT) to understand the relationship between media strategies and audience needs. The results show that Bengkuluekspress.com implements audiovisual content management strategies through four main stages: content planning, video and audio narration production, multiplatform content distribution, and evaluation based on audience engagement data. Audio narration plays an important role in clarifying information and building storytelling that helps viewers understand the news content. Meanwhile, distributing content across various digital platforms such as Facebook, Instagram, YouTube, and TikTok expands reach and increases audience interaction. The challenges faced include strict digital platform regulations, technical production limitations, and content format adjustments for each platform. The study concludes that the strategic use of video and audio narration can significantly enhance audience engagement while strengthening the competitiveness of local online media.